L'Édifice Masonic Memorial Temple. Histoire et architecture maçonniques - Lauzon, Gilles (Ministère de la Culture, des Communications et de la Condition féminine et Direction du patrimoine et de la muséologie, 2010)
Keywords: Francs-Maçons

Les écrits urbains sous contrôle. L'exemple de Montréal - Artières, Philippe (Presses Universitaires de Rennes, 2014)
Keywords: Enseignes; Français; Publicité

"Le Canada est un païs de bois": Forest Resources and Shipbuilding in New France, 1660-1760 - Delaney, Monique (Université McGill, 2003)
The colonial contribution to the French naval shipbuilding industry in the seventeenth and eighteenth centuries, explored within the context of the forest from which the resources for the industry were taken, was a remarkably successful venture that came to an end with the onset of war. In the past, the end of the French naval shipbuilding industry in New France has been attributed to the action or inaction of France that resulted in the inefficient use of forest resources. Issues of interest in, organization or support of colonial efforts by France, however, were nevertheless, limited by the immutable realities of the colonial forest environment. This thesis argues that the success of the industry, considered within the appropriate context, is a consequence of colonial persistence in the face of constraints imposed by the colonial forest environment—despite these other significant issues. The official correspondence, written by colonial officials in New France, record colonial efforts to supply France with timber and detail the development of a naval shipbuilding industry in the colony. These documents provide source material for a case study that demonstrates the constraints imposed by the colonial forests on the experience of colonists, timber suppliers and shipbuilders. The colonial forest was not the same as the forests in France. A simple transfer of knowledge and practice from one forest to another was insufficient to deal with the differences in climate, forest age, tree species and the extent to which human activity affected the different forests. These differences challenged the way in which colonists could use forest resources for their own needs, for export to France and for naval construction. To consider this use of resources, without considering the differences between the available materials in the colony and those available in France, is to look at the story removed from the setting in which it took place. The unique forest in the colony was the setting in which colonial shipbuilding took place. Any study of the development of this industry, or any other industry that relied on forest resources, must give consideration to the constraints and realities of that forest.
Keywords: Construction navale

Déjouer l’ennui au fort de Ville-Marie à Montréal - Pothier, Louise (Revue d'histoire de la Nouvelle-France, 2023)
issued: 2023-21-00
Keywords: Archéologie; Forts

DUNLOP, ALEXANDER FRANCIS - Lachapelle, Jacques (Dictionnaire biographique du Canada, 2005)

Jardiner en Nouvelle-France - Tairraz, Monique (Continuité, 2003)
issued: 2003-23-00
Keywords: Jardins

Les lieux de justice à Montréal sous le Régime français - Robichaud, Léon (Le patrimoine bâti judiciaire de Montréal, 2018)
Keywords: Prisons; Tribunaux

Demeures et positionnement social dans les villes de la Nouvelle-France - Mercier-Méthé, Rosalie (Bulletin d'histoire politique, 2017)
Number: 1
Keywords: Logement

L’agriculture (péri)urbaine: tendances et dynamiques au Québec et en France - Bhatt, Vikram; Bryant, Christopher R.; Loudiyi, Salma (L’état du Québec 2011, 2011)
Keywords: Jardins

Les jardins d'agrément en Nouvelle-France. Étude historique et cartographique - Fortier, Marie-Josée (Les Éditions GID, 2012)
Keywords: Jardins

Jardins d'un autre temps. Deux jardins dans l'esprit de la Nouvelle-France - Tairraz, Monique (Maison Saint-Gabriel et Musée du Château Ramezay, 2001)
Keywords: Alimentation; Jardins; Maison Saint-Gabriel; Ramezay (château de)

Nouvel urbanisme, gentrification et mobilité quotidienne: leçons apprises des quartiers Plateau-Mont-Royal et Bois-Franc… - Barbonne, Rémy (La métropolisation et ses territoires, 2009)
Keywords: Gentrification; Navettage; Plateau Mont-Royal; Quartiers

Le secteur Bois-Franc à Saint-Laurent: l'évaluation environnementale stratégique du plan de réaménagement - Martin, Nadine; Waaub, Jean-Philippe (Les espaces dégradés: contraintes et conquêtes, 2000)
Keywords: Saint-Laurent (ville)

The Sociability of New Urbanism: A Comparative Study of Two Communities in Montreal, Angus Park and Bois-Franc - Pretula, Lesley (Université Concordia, 2003)
Keywords: Quartiers; Rosemont; Saint-Laurent (ville)